Movement discrimination after intra-articular local anaesthetic of the ankle joint. Issue 8 (6th March 2007) - Down, Stuart; Waddington, Gordon; Adams, Roger; Thomson, Malcolm
Abstract : Background: The effect on clinical safety of dampening articular mechanoreceptor feedback at the ankle is unknown. Injection of the ankle joint for pain control may result in such dampening. Athletes receiving intra-articular local anaesthetic may therefore be at increased risk of sustaining ankle injuries, which are a common reason for missed sporting participation. Objective: To determine the effect of intra-articular local anaesthetic on movement discrimination at the ankle joint. Design: Prospective, randomised, double-blinded, placebo-controlled, cross-over trial. Setting: Australian Institute of Sport Medical Centre, Canberra, Australia. Patients: Twenty two healthy subjects (44 ankles) aged 18–26 were recruited for the three visits of the study. Interventions: Subjects were tested for their initial movement discrimination scores using the active movement extent discrimination apparatus (AMEDA). They then received ultrasound-guided intra-articular injections of local anaesthetic (2% lignocaine hydrochloride) or normal saline, on two separate later occasions, before further AMEDA assessment. Main outcome measures: Change in movement discrimination scores after intra-articular injection of local anaesthetic or saline. Results: Movement discrimination scores were not significantly different from control ankles after injection of either local anaesthetic or saline into the ankle joint. Conclusions: The intra-articular injection of neither 2 ml lignocaine nor an equivalent amount of normal saline resulted in significant effects on movement discrimination at the ankle joint. These results suggest that injections of local anaesthetic into the ankle joint are unlikely to significantly affect proprioception and thereby increase injury risk.